Prenatal exposures and the development of childhood wheezing illnesses. Issue 2 (April 2017) - Rosas-Salazar, Christian; Hartert, Tina V.
Abstract : Purpose of review: To critically evaluate and summarize studies published between July 2015 and June 2016 linking prenatal exposures and the onset of childhood wheezing illnesses and to discuss future research directions in this field. Recent findings: The aggregated evidence indicates a consistent detrimental effect of prenatal exposure to parental smoking, outdoor air pollution, and maternal stress on childhood wheezing illnesses. Less consistent evidence suggests an adverse impact of maternal obesity during pregnancy and prenatal exposure to antibiotics on these outcomes. There is insufficient evidence to support an association between in-utero exposure to acetaminophen or prenatal levels of specific nutrients (such as vitamin D, folic acid, or polyunsaturated fatty acids) and childhood wheezing illnesses. Summary: Several common potentially modifiable prenatal exposures appear to be consistently associated with childhood wheezing illnesses (e.g. parental smoking, outdoor air pollution, and maternal stress). However, the effect of many other prenatal exposures on the onset of childhood wheezing illnesses remains unclear. The existing scientific evidence from the past year does not allow us to make any new recommendations on primary prevention measures. Intervention studies will best demonstrate whether changing the prenatal environment can prevent childhood wheezing illnesses and asthma.